Dampak Keterlambatan Penyampaian LPJ Terhadap Penyajian Laporan Keuangan KPPN Provinsi Sumatera Utara - Intan Sari Tanjung; Nurhayati Nurhayati (Universitas Muhammadiyah Enrekang, 2022)
This study discussed the impact of delay submitting accountability Conducted by the work unit. Prepare an accountability report is an obligation for a treasurer of the work unit to be delivered to the KPPN for accountability of the money it manages. The treasurer of the work unit is required to submit its accountability report the following month after the funds received from the KPPN and managed. The goals of this study is to know how is the procedure of reporting responsibility submitted the impact that resulted from the delay in submitting report of accountability to presentation of financial report of KPPN Provsu.